Electric City : General Electric in Schenectady - Blackwelder, Julia Kirk, 1943- (Book collections on Project MUSE., 2014)
For seven decades the General Electric Company maintained its manufacturing and administrative headquarters in Schenectady, New York. Electric City: General Electric in Schenectady explores the history of General Electric in Schenectady from the company's creation in 1892 to the present. As one of America's largest and most successful corporations, GE built a culture centered around the social good of technology and the virtues of the people who produced it. At its core, GE culture posited that engineers, scientists, and craftsmen engaged in a team effort to produce technologically advanced ma.